De la collectivité-territoire à la collectivité dans le territoire - Emilie Ruin (L'Espace Politique)
This article proposes to decrypt the mechanisms of public action’s contribution and integration into the Territorial Intelligence’s construction. It is based on three examples, Ardennes, Rhône and Vaucluse and hypotheses that they are at three ages of this construction from the less until the most developed. This analysis is founded on four nested stages, from the territorial ability to attract the individual knowledge and know-how, to create structures relating individual to collective knowledge, to create inter-organisational relations habits and go further with voluntary collaborations.